Efektivitas Penggunaan Portofolio pada Perkuliahan Mikrobiologi Terhadap Kemandirian dan Hasil Belajar Mahasiswa - Lubis, Shofia; Hasruddin, Hasruddin; Mahmud, Mahmud (Magister Pendidikan Biologi, Universitas Negeri Medan, 2016)
This research study aimed to know the effectiveness of portfolio assessment in microbiology course on studentsâ self-regulated and learning outcome. This research was the experimental research of the pretes-posttest group design. The sample was 44 students of Nondik Biologi 2013. Self-regulated questionnaire and learning outcome test were used to measure self-regulated and learning outcome of students. Data were analyzed by using independent sample t-test with SPSS statistics 21 program. The results show that: (1) Studentsâ self regulated learning that assessed by portfolio bigger than assessed by paper test (tcount=3,105, p<0,05), the average score of studentsâ regulated learning on experimental class (score 81) > students on control class (score 76); (2) Studentsâ learning outcome that assessed by portfolio higher than assessed by paper test (tcount=2,861, p<0,05), the average score of studentsâ learning outcome on experimental class (score 86) > students on control class (score 80); (3) Effect size portofolio assessment application on studentsâ self regulated and learning outcome isÂ 93% dan 81%, for each. This study conclude that portfolio assessment application effective on studentsâ self regulated and learning outcome in experimental microbiology, State University of Medan.